Micropropagation of Melissa officinalis L. through proliferation of axillary shoots - Tavares, A. C. (1996)
Multiple shoots were differentiated in cotyledonary nodes of 10 d old seedlings of Melissa officinalis, cultured on MS medium supplemented with BAP (0-4 mg/l). The production of shoots was further induced in subcultures of the original explant, after the first harvest of shoots (stumps), using similar conditions. The highest average number of shoots in the two inoculations was obtained with 2 mg/l of BAP: 24 axillary shoots per explant, 7 in the first inoculation and 17 in the second one. The maximum elongation of shoots was achieved with BAP at 0.2 mg/l, and higher concentrations of the hormone induced a decrease in their size. A range of BAP concentrations between 0.2 - 0.5 mg/l allowed the production of more shoots with a size suitable for rooting. Roots were induced in 30d old shoots, transferred to MS medium individually supplemented with IBA or NAA (0 - 4 mg/l). Micropropagated plants were successfully transferred to soil.